Cancer in deceased adults with intellectual disabilities: English population-based study using linked data from three sources. Issue 3 (24th March 2022) - Heslop, Pauline; Cook, Adam; Sullivan, Brian; Calkin, Rachel; Pollard, Johanna; Byrne, Victoria
Abstract : Objective: To improve our understanding of cancer in adults with intellectual disabilities. Design: Population-based study using linked data about deceased adults from the Learning (Intellectual) Disabilities Mortality Review (LeDeR) programme, the national cancer registry and NHS Digital. Setting: England. Participants: 1096 adults with intellectual disabilities identified by the LeDeR programme who died between 1 January 2017 and 31 December 2019. Outcome measure: Any form of cancer listed as a long-term health condition by a LeDeR reviewer or 10th edition of the International Classification of Diseases codes C00–D49 included on Parts I or II of the Medical Certificate of Cause of Death. Results: In decedents with intellectual disabilities and cancer, more than a third (35%; n=162) had cancer diagnosed via emergency presentations. Almost half (45%; n=228) of cancers were at stage IV when diagnosed. More than a third (36%; n=309) of underlying causes of deaths were of cancers of the digestive system; almost half of these (48%; n=147) were cancer of the colon, rectum or anus. Of those who died with colorectal cancer, 43% were below the age threshold for colorectal screening. Conclusions: In decedents with intellectual disabilities, symptoms suggestive of cancer had tended to be identified most frequently as an emergency and at a late stage. There is a need for greater awareness of symptoms of cancer in this population, a lower threshold for referral by General Practitioners (GPs), accelerated access to diagnosis and treatment and consideration paid to lowering the age for colorectal screening.